Deconstructing history - Munslow, Alun 1947- (London New York Routledge, 2006)
Munslow provides an introduction to the debates and issues of postmodernist history and surveys the latest research into the relationship between the past, history and historical practice. A glossary of key terms is included.
Introduction -- The past in a changing present -- History as reconstruction/construction -- History as deconstruction -- What is wrong with deconstructionist history? -- What is wrong with reconstructionist/constructionist history? -- Michel Foucault and History -- Hayden White and deconstructionist history -- Conclusion.
Includes bibliographical references (p. [207]-239) and index.
Keywords: History -- Methodology; Historiography; History -- Philosophy; Narration (Rhetoric); Literature and history